2015 7th International Conference on Communication Systems and Networks (COMSNETS) 2015
DOI: 10.1109/comsnets.2015.7098725
|View full text |Cite
|
Sign up to set email alerts
|

Innovation for crop quality certification using ICT

Abstract: The focus of Indian agriculture so far has been on meeting the national demand, however it is going through a steady transformation phase to address the global requirement and is being driven by consumers and markets. According to APEDA Agriexchange portal, every year our country suffers more than 17000 Cr losses because consignments get rejected [I]. There is a growing concern for the food quality and scrutiny of the food supply chain [2] due to increased use of pesticides and its impact on health [3].As a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The sustainable agricultural production is constrained by factors like growing population, water shortages, declining soil fertility and climate change [8]. Recently scientists have been exploring technologies such as Wireless sensor technologies [9] and ICT [10] for Sustainable agricultural production The sustainable development goals listed in the previous section are ambitious in terms of number, scope, and indicators used to measure the attainment of these goals. One of the effective ways to achieve the set targets is through innovative use of existing and emerging technologies.…”
Section: Sectors For Humanitarian Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…The sustainable agricultural production is constrained by factors like growing population, water shortages, declining soil fertility and climate change [8]. Recently scientists have been exploring technologies such as Wireless sensor technologies [9] and ICT [10] for Sustainable agricultural production The sustainable development goals listed in the previous section are ambitious in terms of number, scope, and indicators used to measure the attainment of these goals. One of the effective ways to achieve the set targets is through innovative use of existing and emerging technologies.…”
Section: Sectors For Humanitarian Engineeringmentioning
confidence: 99%
“…The sustainable agricultural production is constrained by factors like growing population, water shortages, declining soil fertility and climate change [8]. Recently scientists have been exploring technologies such as Wireless sensor technologies [9] and ICT [10] for Sustainable agricultural production Newer clean and green technologies need to be developed and adopted, especially in the areas of civil engineering, construction, water management, urban development, and for maintaining biodiversity [15].…”
Section: Sectors For Humanitarian Engineeringmentioning
confidence: 99%
“…ICTs in agriculture could potentially increase the efficiency, productivity and sustainability through offering information and knowledge. In recent years, smart farming for agriculture [33]- [40] makes a tremendous contribution for food sustainability. For example, using wireless sensor network in farming from independent power source distribution, monitoring irrigation valves and switches operation, and remote area control will effectively improve the production of excellent quality farm products.…”
Section: A Sustainable Life For Humanity 1) End Of Poverty In Life An...mentioning
confidence: 99%
“…In particular, using fuzzy logic for decision making in power control distribution for the entire system results in power savings. Singh et al [40] have developed a solution for agriculture process standards implementation that benefits the quality and quantity of the product. Using a so-called mKRISHI-GAP system, the authors in [40] demonstrated the field experiences in implementation of good agriculture practices certification in Amravati district for orange producer group.…”
Section: A Sustainable Life For Humanity 1) End Of Poverty In Life An...mentioning
confidence: 99%